Investigation on the plasticity accumulation of Ti-6Al-4V fretting wear by decoupling the effects of wear and surface profile in finite element modelling - Tobi, A.L. Mohd; Sun, Wei; Shipway, P.H. (Elsevier, 2016)
A finite-element-based wear modelling methodology and a computational device for decoupling wear effects is presented in this study. The decoupling of wear effects facilitates the capture of plasticity accumulation on a particular wear-scarring profile after a specific number of cycles. It was determined that significant plasticity accumulation due to plastic shakedown was predicted in a partial-slip case, while a saturation of plastic deformation was predicted in a gross-sliding case. It was also predicted that a significant amount of plasticity does not meaningfully contribute to the stress and strain range observed in the contact region. It was assumed that plasticity accumulation contributes towards wear of the material and feeds the stress changes, which indirectly affects fatigue life.